Poems of the sea - McClatchy, J. D., 1945- (New York : Distributed by Random House, 2001)
Presents a collection of poems based on the theme of the sea, including selections by Edgar Allan Poe, Shakespeare, Homer, Sylvia Plath, and many others.
Includes index.
Adult
Keywords: Sea poetry; Sea poetry -- Translations into English; Sea poetry